Epigenetics of sex determination and gonadogenesis. Issue 4 (8th February 2013) - Piferrer, Francesc
<x xml:space="preserve">Abstract</x> Epigenetics is commonly defined as the study of heritable changes in gene function that cannot be explained by changes in DNA sequence. The three major epigenetic mechanisms for gene expression regulation include DNA methylation, histone modifications, and non‐coding RNAs. Epigenetic mechanisms provide organisms with the ability to integrate genomic and environmental information to modify the activity of their genes for generating a particular phenotype. During development, cells differentiate, acquire, and maintain identity through changes in gene expression. This is crucial for sex determination and differentiation, which are among the most important developmental processes for the proper functioning and perpetuation of species. This review summarizes studies showing how epigenetic regulatory mechanisms contribute to sex determination and reproductive organ formation in plants, invertebrates, and vertebrates. Further progress will be made by integrating several approaches, including genomics and Next Generation Sequencing to create epigenetic maps related to different aspects of sex determination and gonadogenesis. Epigenetics will also contribute to understand the etiology of several disorders of sexual development. It also might play a significant role in the control of reproduction in animal farm production and will aid in recognizing the environmental versus genetic influences on sex determination of sensitive species in a global change scenario. Developmental Dynamics 242:360–370, 2013. © 2013 Wiley Periodicals, Inc.